Expert System in Detecting Rice Plant Diseases Using Certainty Factor - Minarni, Minarni; Fadhillah, Anisah (-)
The livelihoods of most people in Indonesia are cultivate rice which is the staple food for the people of Indonesia. The productivity of rice plants can be obstructed when rice attacks disease. Diseases can be addressed from young if farmers know how to handle it. In fact, farmers are difficult to obtain knowledge about the disease of rice caused by a lack of trainers and the limited amount of time trainers. To resolve these problems, teh one of the solution is to make an expert system application, the system adopts the knowledge from an expert / counselor. For the decision of this application, itâs using certainty factor. The certainty factor is a method that uses weights certainty assumption of an expert in rice plants. The output is given in the form of images, the solution, as well as the percentage of the rice plant diseases conviction. The output is obtained from the results of the consultations that conducted by user. Users must answer the questions in the form of symptoms of the disease. In the design of this applications making by using the PHP programming and used a MySQL database. Applications make based on the WEB. The results of the research has been done is about 60% of respondents found that this application helpful to use or for the needs of the farmers, and approximately 78% found that this application is have an interesting features.